Diversification Strategy and Good Governance: Does It Affect Firm’s Leverage? - Katiya Nahda; Azaria Lionara Rahmadana (Jurnal Keuangan dan Perbankan, 2021)
This paper aims to analyze whether firm diversification affects firm leverage in developing countries. This research model is based on the agency theory view that focuses on diversification in leverage through good governance mechanisms. The data comes from 43 companies from 215 observation companies listed on the Indonesia Stock Exchange in the 2014–2018 period, supporting the co-insurance hypothesis; our findings suggest a positive effect of diversification on debt levels. Our findings show that cost advantages occur in diversified firms, including higher debt ratios in the firm’s capital structure. These effects are more substantial when firms have better corporate governance. These findings add value to the existing literature on the relationship between firm diversification, corporate management, and leverage and can be helpful for managers and policy-makers regarding the evaluation of diversification strategy and corporate governance implementations in Indonesia that has been widely studied.DOI: 10.26905/jkdp.v25i3.5758